Current knowledge and recent insights into the genetic basis of amyotrophic lateral sclerosis - Volk, Alexander E.; Weishaupt, Jochen H.; Andersen, Peter M.; Ludolph, Albert C.; Kubisch, Christian (Medizinische Genetik, 2018)
Amyotrophic lateral sclerosis (ALS) is the most frequent motor neuron disease, affecting the upper and/or lower motor neurons. However, extramotor symptoms can also occur; cognitive deficits are present in more than 40% of patients and 5-8% of ALS patients develop frontotemporal dementia. There is no effective treatment for ALS and median survival is 2-3 years after onset., Amyotrophic lateral sclerosis is a genetically heterogeneous disorder with monogenic forms as well as complex genetic etiology. Currently, complex genetic risk factors are of minor interest for routine diagnostic testing or counseling of patients and their families. By contrast, a monogenic cause can be identified in 70% of familial and 10% of sporadic ALS cases. The most frequent genetic cause is a noncoding hexanucleotide repeat expansion in the C9orf72 gene. In recent years, high-throughput sequencing technologies have helped to identify additional monogenic and complex risk factors of ALS., Genetic counseling should be offered to all ALS patients and their first- and possibly second-degree relatives, and should include information about the possibilities and limitations of genetic testing. Routine diagnostic testing should at least encompass the most frequently mutated disease genes (C9orf72, SOD1, TDP-43, FUS). Targeted sequencing approaches including further disease genes may be applied. Caution is warranted as the C9orf72 repeat expansion cannot be detected by routine sequencing technologies and testing by polymerase chain reaction (PCR) is failure-prone., Predictive testing is possible in families in which a genetic cause has been identified, but the limitations of genetic testing (i.e., the problems of incomplete penetrance, variable expressivity and possible oligogenic inheritance) have to be explained to the families.
Gesehen am 09.07.2021